2019
DOI: 10.3847/1538-4357/ab1e4e
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Atomic and Molecular Hydrogen with a Diamond-like Carbon Surface: H2 Formation and Desorption

Abstract: The interactions of atomic and molecular hydrogen with bare interstellar dust grain surfaces are important for understanding H2 formation at relatively high temperatures (> 20 K). We investigate the diffusion of physisorbed H-atoms and the desorption energetics of H2 molecules on an amorphous diamondlike carbon (DLC) surface. From temperature-programmed desorption experiments with a resonance-enhanced multiphoton ionization (REMPI) method for H2 detection, the H2 coverage-dependent activation energies for H2 d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 71 publications
(105 reference statements)
0
21
1
Order By: Relevance
“…69,70) Recently, we successfully produced a hydrogen-free DLC surface by the laser ablation method and investigated the H (D) atom diffusion processes on it. 34) We found that the H atoms on DLC cannot be detected by the PSD-REMPI method, in contrast to those demonstrated for ASW and CO surfaces. 30,33) Instead, we decided to monitor the surface number density of H2 upon H atom deposition to extract information on the H atom diffusion.…”
Section: Behavior Of H (D) Atoms On Diamond-like Carboncontrasting
confidence: 79%
See 1 more Smart Citation
“…69,70) Recently, we successfully produced a hydrogen-free DLC surface by the laser ablation method and investigated the H (D) atom diffusion processes on it. 34) We found that the H atoms on DLC cannot be detected by the PSD-REMPI method, in contrast to those demonstrated for ASW and CO surfaces. 30,33) Instead, we decided to monitor the surface number density of H2 upon H atom deposition to extract information on the H atom diffusion.…”
Section: Behavior Of H (D) Atoms On Diamond-like Carboncontrasting
confidence: 79%
“…Recently, using a combination of photostimulated desorption (PSD) 29) and resonance-enhanced multiphoton ionization (REMPI) methods, we were successful in monitoring hydrogen on ASW, 30,31) polycrystalline ice (PCI), [30][31][32] pure solid CO, 33) and diamond-like carbon. 34) In the following sections, a summary of these experiments is provided after the description of the PSD-REMPI method. Additionally, as our new experimental findings relevant to the hydrogen diffusion, a proton-hole transfer that delivers a negative charge through ice is presented (Sect.…”
Section: Introductionmentioning
confidence: 99%
“…We obtained the binding energy distribution of H 2 by considering zero-point energy difference between D 2 and H 2 , 3.15 meV (Amiaud et al 2015). Note that laboratory experiments have found that o-D 2 is bound to surfaces slightly more strongly than p-D 2 (∼1 meV) (Amiaud et al 2008;Tsuge et al 2019), but we neglect the difference in this work for simplicity. The hopping activation energy from a site with the binding energy of E b to another site with the binding energy of E b (E hop ) is given as follows (Cazaux et al 2017, see their Fig.…”
Section: Binding Energy Distribution Hopping Activation Energy and mentioning
confidence: 99%
“…Because diamond-like carbon (DLC) is a good analogue for potential C-dominated ISM dust, we investigated the behaviour of H atoms on DLC (Tsuge et al 2019). The DLC surface was prepared on the aluminium substrate by the laser ablation of a graphite disk in situ within the experimental chamber to avoid contamination in air.…”
Section: Behaviour Of H (D) Atoms On Diamond-like Carbonmentioning
confidence: 99%
“…For deuterium, the D 2 intensities for D atom deposition are always below those for D 2 deposition, indicating that the diffusion of D atoms is sufficiently slower than that of H atoms. A more detailed analysis has been presented elsewhere (Tsuge et al 2019).…”
Section: Behaviour Of H (D) Atoms On Diamond-like Carbonmentioning
confidence: 99%